The efficacy of ferroptosis-inducing compounds IKE and RSL3 correlates with the expression of ferroptotic pathway regulators CD71 and SLC7A11 in biliary tract cancer cells. - Dino Bekric; Tobias Kiesslich; Matthias Ocker; Martina Winklmayr; Markus Ritter; Heidemarie Dobias; Marlena Beyreis; Daniel Neureiter; Christian Mayr (PLoS ONE, 2024)
Introduction Biliary tract cancer (BTC) is a lethal disease with a bad overall survivability, partly arising from inadequate therapeutic alternatives, detection at a belated stage, and a resistance to common therapeutic approaches. Ferroptosis is a form of programmed cell death that depends on reactive oxygen species (ROS) and iron, causing excessive peroxidation of polyunsaturated fatty acids (PUFAs). Therefore, the objective of this investigation is, whether ferroptosis can be induced in BTC in vitro and whether this induction is dependent on specific molecular markers. Methods The study conducted resazurin assay and IC25/50 calculation to explore the possible cytotoxic outcomes of different classes of ferroptosis-inducing substances (FINs) on a comprehensive in vitro model of 11 BTC cell lines. Combinatory treatments with different cell death inhibitors were performed to evaluate the magnitude of ferroptosis induction. To ascertain whether ferroptotic cell death occurred, liperfluo and iron assay kits were employed to evaluate lipid ROS and intracellular iron abundance. Potential biomarkers of ferroptosis sensitivity were then assessed via western blot analysis, a rtPCR panel and functional assay kits. Results The study found that different FINs reduced cell viability in a cell line-dependent manner. In addition, we measured increased lipid ROS and intracellular Fe2+ levels upon exposure to FINs in BTC cells. Combining FINs with inhibitors of ferroptosis, necroptosis or apoptosis suggests the occurrence of ferroptotic events in BTC cell lines CCC-5, HuH-28 and KKU-055. Furthermore, we found that BTC cells display a heterogeneous profile regarding different molecular genes/markers of ferroptosis. Subsequent analysis revealed that sensitivity of BTC cells towards IKE and RSL3 positively correlated with CD71 and SLC7A11 protein expression. Conclusion Our results demonstrate that induction of ferroptosis is a promising approach to inhibit BTC cell growth and that the sensitivity of BTC cells towards ferroptosis induction might be dependent on molecular markers such as CD71 and SLC7A11.